To find the sum of two numbers in scientific notation, we need to have the same exponent.
5.6 x 10^3 = 5600
2.4 x 10^3 = 2400
Now, we can add the numbers:
5600 + 2400 = 8000
The sum of 5.6 x 10^3 and 2.4 x 10^3 is 8000.
the sum of 5.6 x 10^3 and 2.4 x 10^3 is?
7 answers
thats wrong
I apologize for the mistake. Let's recalculate the sum of 5.6 x 10^3 and 2.4 x 10^3:
To add these numbers, we need to make their exponents the same.
5.6 x 10^3 = 5.6 x 1000 = 5600
2.4 x 10^3 = 2.4 x 1000 = 2400
Now that both numbers have the same exponent, we can add them:
5600 + 2400 = 8000
So, the correct sum of 5.6 x 10^3 and 2.4 x 10^3 is 8000.
To add these numbers, we need to make their exponents the same.
5.6 x 10^3 = 5.6 x 1000 = 5600
2.4 x 10^3 = 2.4 x 1000 = 2400
Now that both numbers have the same exponent, we can add them:
5600 + 2400 = 8000
So, the correct sum of 5.6 x 10^3 and 2.4 x 10^3 is 8000.
8.0 x 10^3 minus 2.0 x 10^3 =
To subtract numbers in scientific notation, we need to have the same exponent.
8.0 x 10^3 = 8000
2.0 x 10^3 = 2000
Now, we can subtract the numbers:
8000 - 2000 = 6000
So, the result of 8.0 x 10^3 minus 2.0 x 10^3 is 6000.
8.0 x 10^3 = 8000
2.0 x 10^3 = 2000
Now, we can subtract the numbers:
8000 - 2000 = 6000
So, the result of 8.0 x 10^3 minus 2.0 x 10^3 is 6000.
(2.6 x 10^6) + (3.4 x 10^3)
To add numbers in scientific notation, we need to make sure they have the same exponent.
2.6 x 10^6 = 2,600,000
3.4 x 10^3 = 3,400
Now, we can add the numbers:
2,600,000 + 3,400 = 2,603,400
Therefore, the sum of (2.6 x 10^6) + (3.4 x 10^3) is 2,603,400.
2.6 x 10^6 = 2,600,000
3.4 x 10^3 = 3,400
Now, we can add the numbers:
2,600,000 + 3,400 = 2,603,400
Therefore, the sum of (2.6 x 10^6) + (3.4 x 10^3) is 2,603,400.